Carbon‐sensitive pedotransfer functions for plant available water. Issue 3 (30th March 2022) - Bagnall, Dianna K.; Morgan, Cristine L. S.; Cope, Michael; Bean, Gregory M.; Cappellazzi, Shannon; Greub, Kelsey; Liptzin, Daniel; Norris, Charlotte L.; Rieke, Elizabeth; Tracy, Paul; Aberle, Ezra; Ashworth, Amanda; et al.
Abstract: Currently accepted pedotransfer functions show negligible effect of management‐induced changes to soil organic carbon (SOC) on plant available water holding capacity (θAWHC ), while some studies show the ability to substantially increase θAWHC through management. The Soil Health Institute's North America Project to Evaluate Soil Health Measurements measured water content at field capacity using intact soil cores across 124 long‐term research sites that contained increases in SOC as a result of management treatments such as reduced tillage and cover cropping. Pedotransfer functions were created for volumetric water content at field capacity (θFC ) and permanent wilting point (θPWP ). New pedotransfer functions had predictions of θAWHC that were similarly accurate compared with Saxton and Rawls when tested on samples from the National Soil Characterization database. Further, the new pedotransfer functions showed substantial effects of soil calcareousness and SOC on θAWHC . For an increase in SOC of 10 g kg –1 (1%) in noncalcareous soils, an average increase in θAWHC of 3.0 mm 100 mm –1 soil (0.03 m 3  m –3 ) on average across all soil texture classes was found. This SOC related increase in θAWHC is about double previous estimates. Calcareous soils had an increase in θAWHC of 1.2 mm 100 mm –1 soil associated with a 10 g kg –1 increase in SOC, across all soil texture classes. New equations can aid in quantifying benefits of soil management practices that increase SOC and can be used to model the effect of changes in management on drought resilience. Core Ideas: New pedotransfer functions show organic C increases plant available water. Noncalcareous soils show greater effects of organic C on plant available water. Increase in plant available water from organic C is more than double previous estimates. These pedotransfer functions can easily be used in hydrologic models. A gap is bridged for modeling the effect of increased soil organic C on plant available water.